Celastrol protects human retinal pigment epithelial cells against hydrogen peroxide mediated oxidative stress, autophagy, and apoptosis through sirtuin 3 signal pathway. Issue 6 (7th January 2019) - Du, Zhaojiang; Zhang, Wen; Wang, Shengyu; Zhang, Jing; He, Jingang; Wang, Yuan; Dong, Yuhong; Huo, Min
Abstract: Age‐related macular degeneration (AMD), one of the most common causes of visual impairment, often occurrs in the elderly in developed countries. Oxidative stress, autophagy, and apoptosis of retinal pigment epithelial (RPE) cells play roles in the pathogenesis of AMD. In the current study, the protective effect of celastrol against hydrogen peroxide (H2 O2 )‐induced oxidative stress and apoptosis was investigated using a human RPE cell line (ARPE‐19). H2 O2 inhibited ARPE‐19 cells' survival and autophagy and induced their oxidative stress and apoptosis. Compared with the H2 O2 group, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) assay showed that celastrol increased ARPE‐19 cells' survival in a dose‐ and time‐dependent manner. Further, studies have suggested that celastrol has antioxidative stress and antiapoptosis effects in H2 O2 ‐treated ARPE‐19 cells. Also, cell autophagy is activated by celastrol in H2 O2 ‐treated ARPE‐19 cells. Reverse transcription polymerase chain reaction and Western blot showed that celastrol elevated the messenger RNA (mRNA) and protein expression of sirtuin 3 (SIRT3) in H2 O2 ‐induced ARPE‐19 cells. Inhibition of the level of SIRT3 by SIRT3 small interfering RNA (siRNA) reversed the effects of celastrol on oxidative stress, autophagy, and apoptosis in H2 O2 ‐induced ARPE‐19 cells. In conclusion, these observations suggest that celastrol activates the SIRT3 pathway in RPE cells and protects against H2 O2 ‐induced oxidative stress and apoptosis. Abstract : Celastrol activates the SIRT3 pathway in RPE cells and protects against H2 O 2 ‐induced oxidative stress and apoptosis.